Optimized design and performance analysis of novel comparator and full adder in nanoscale. Issue 1 (31st December 2016) - Abdullah-Al-Shafi, Md.; Bahar, Ali Newaz
Abstract: In a vastly rapid progress of very large scale integration (VLSI) archetype, it is the requirement of moment to attain a consistent model with swifter functioning speed and low power utilization. Quantum-dot Cellular Automata (QCA) is an inimitable transistorless computation approach that is based on semiconductor substantial and a substitute for customary CMOS and VLSI archetype at nanoscale point which comprises a better switching frequency, enhanced scale integration and small extent. In the design of digital logic, a comparator is the essential forming component which implements the resemblance of two numbers and a binary full adder is a major entity in digital logic systems. This paper deals with an expanded layout of reversible 1-bit comparator and proficient full adder without wire-crossing in QCA. The proposed layouts are significantly declined in terms of area and cell complexity, assessed to other layouts and clock cycle is retained at least. Quantum costs of the proposed circuits are estimated and compared, that shows the proposed QCA layouts have lesser quantum cost equated to regular designs and the energy depletion by the circuits endorses the view of QCA nano-circuit attending as a substitute level for the completion of reversible computing. Under thermal unpredictability, the constancy of the proposed designs is evaluated which show the operating efficacy of the designs. The simulation outcomes in QCADesigner tool approve that the presented designs performs properly and can be operated as an extreme performing design in QCA technology.